Naczynie z wyobrażeniami ptaków z Woli Łobudzkiej, stan. 1, gmina Szadek - Blaszczyk, Jacek (Acta Universitatis Lodziensis. Folia Archaeologica, 1997)
As a result of three-season conducted rescue researches 106 grave complexes were revealed. Materials from 49 graves are stored in Museum of Pabianice whereas furnishing of 57 graves in the collection of the Chair of Archaeology in the University of Łódź. There is the vessel with the picture of birds uncovered in the grave no 3 that deserves our attention. A grave pit had an oval shape of 50 cm diameter. A filling of the pit consisted of dark gray sand with a large amount of charcoal. Six coarse fragments of vessels (Tab. II, Figs. 1-6) and fragments with the picture of birds (Tab. III, Figs. 1, 2a-c) were found in the upper part of the filling in a layer 10-15 cm thick. At the bottom of the pit a cinerary urn was placed while above it an umbo and fragments of a shield handle were ucovered. Artifacts found in the grave have numerous analogies. On the basis of these the complex is dated from the 2nd half of the 3rd century to the 1st half of the 4th century (phases C2 -C3). It is difficult to interpret an idea of the picture from the vessel no 7. The picture made by one stamp (preasumbly traces of an ornament) shows birds floating on water. The birds differ by numbers of visible details, but it is hard to ascertain whether it is intentional idea or coarse vessel making. Ethnographic sources provide much information about the meaning of animals in folk beliefs. Birds emerging in beliefs e.g. in Slovenia and Belorussia are connected with a cult of the dead. The possibility of linking the pattern from the Wola Łobudzka vessel with beliefs where birds play an important role can not be excluded. However, the problem of beliefs connected with animals functioning in prahistory is too wide to be covered in this paper.